2000
DOI: 10.1046/j.1365-2141.2000.02251.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced factor XII levels in patients with the antiphospholipid syndrome are associated with antibodies to factor XII

Abstract: Summary. Antibodies to factor XII (FXII) have previously been identified in some patients who were lupus anti-coagulantpositive. The relationship between these antibodies and FXII levels appeared to be variable. The aim of the present study was to confirm the presence of antibodies to FXII in patients with well characterized antiphospholipid syndrome (APS) and to establish their potential effect on levels of FXII. Forty-two patients with APS were studied; 21 patients were found to have either immunoglobulin (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 26 publications
0
41
0
2
Order By: Relevance
“…62 When evaluating clinical data on factor XII, it is important to note that antibodies to factor XII and reduced factor XII levels have been associated with antiphospholipid antibodies (APA) and the prothrombitic APA syndrome. 63,64 APAs are relatively common in the general population, and it is possible that they are over-represented in patients with apparent low to low-normal factor XII levels. At this point the available data do not allow us to firmly conclude that factor XII contributes positively or negatively to thrombotic disease in humans.…”
Section: Intrinsic Pathway Proteins and Thromboembolic Disease In Humansmentioning
confidence: 99%
“…62 When evaluating clinical data on factor XII, it is important to note that antibodies to factor XII and reduced factor XII levels have been associated with antiphospholipid antibodies (APA) and the prothrombitic APA syndrome. 63,64 APAs are relatively common in the general population, and it is possible that they are over-represented in patients with apparent low to low-normal factor XII levels. At this point the available data do not allow us to firmly conclude that factor XII contributes positively or negatively to thrombotic disease in humans.…”
Section: Intrinsic Pathway Proteins and Thromboembolic Disease In Humansmentioning
confidence: 99%
“…От-мечено, что дефицит фактора XII в редких случаях связан с циркуляцией в плазме антифосфолипидных антител. Это объясняется тем, что при антифосфоли-пидном синдроме в плазме присутствуют антитела не только к фосфолипидам, но и к фосфолипид-про-теиновым комплексам (прекалликреин, факторы XI и XII) [76][77][78].…”
Section: тромбофилия и беременностьunclassified
“…Recently, Jones et al found both IgM and IgG antibodies to FXII in the plasma of women with antiphospholipid syndrome and IRM, pointing to an autoimmune basis of reduced FXII activity in these women. 10 Factor XII is involved in the initiation of the intrinsic pathway of blood coagulation, fibrinolysis, the generation of bradykinin and the complement system. In some studies elevated plasma levels of FXII have been reported to be associated with coronary heart disease and acute myocardial infarction, 5 whereas others found no effect.…”
Section: Discussionmentioning
confidence: 99%